2023
DOI: 10.1161/atvbaha.123.319251
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Mitigates Endothelial Pyroptosis and Atherosclerosis by Downregulating NEAT1 Through N6-Methyladenosine Modifications

Abstract: BACKGROUND: The benefits of exercise on the cardiovascular system are widely recognized; however, the underlying mechanisms are unknown. Here, we report the effect of the long noncoding RNA NEAT1, which is regulated by exercise, on atherosclerosis development after N6-methyladenosine (m6A) modifications. METHODS: Using clinical cohorts and NEAT1 −/− mice, we determined the exercise-mediated expression and role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…A study found that voluntary wheel running, a natural type of aerobic exercise in the murine model could decrease the protein levels of the inflammasome components and markedly inhibit the caspase-1 activity in endothelial cells within the aorta of mice fed with a high-fat diet (HFD) (Lee et al, 2020). Recently, another study has demonstrated that exercise-induced a significant downregulation of m6A modification and methyltransferase-like 14 (Yang et al, 2023). This protein binds to the m6A sites of nuclear paraspeckle assembly transcript 1 (NEAT1) and promotes NEAT1 expression through subsequent YT521-B homology domain-containing 1, which transcriptionally promotes NLRP3 expression and endothelial pyroptosis (Yang et al, 2023).…”
Section: Exercise Improves As and Inhibits Nlrp3 Inflammasomementioning
confidence: 99%
See 2 more Smart Citations
“…A study found that voluntary wheel running, a natural type of aerobic exercise in the murine model could decrease the protein levels of the inflammasome components and markedly inhibit the caspase-1 activity in endothelial cells within the aorta of mice fed with a high-fat diet (HFD) (Lee et al, 2020). Recently, another study has demonstrated that exercise-induced a significant downregulation of m6A modification and methyltransferase-like 14 (Yang et al, 2023). This protein binds to the m6A sites of nuclear paraspeckle assembly transcript 1 (NEAT1) and promotes NEAT1 expression through subsequent YT521-B homology domain-containing 1, which transcriptionally promotes NLRP3 expression and endothelial pyroptosis (Yang et al, 2023).…”
Section: Exercise Improves As and Inhibits Nlrp3 Inflammasomementioning
confidence: 99%
“…Recently, another study has demonstrated that exercise-induced a significant downregulation of m6A modification and methyltransferase-like 14 (Yang et al, 2023). This protein binds to the m6A sites of nuclear paraspeckle assembly transcript 1 (NEAT1) and promotes NEAT1 expression through subsequent YT521-B homology domain-containing 1, which transcriptionally promotes NLRP3 expression and endothelial pyroptosis (Yang et al, 2023). As a result, exercise effectively inhibits NLRP3 expression and endothelial pyroptosis, preventing AS plaque formation (Yang et al, 2023).…”
Section: Exercise Improves As and Inhibits Nlrp3 Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, down-regulation of METTL14 reduces its binding to the m6A site of NEAT1 and subsequently promotes NEAT1 expression through YTHDC1 recognition. In addition, NEAT1 promotes transcriptional activation of NLRP3 by binding to KLF4 (Kruppel-like factor 4), which ultimately promotes the pyroptosis of endothelial cells [ 90 ]. However, in the tissues of renal cell carcinoma (RCC), METTL14 regulates the expression of NEAT1 through another recognition protein YTHDF2.…”
Section: Epigenetic Modifications In Different Cell Death Modesmentioning
confidence: 99%
“…Notably, m 6 A modification is perceived to regulate a wide spectrum of RNA biology including splicing, nuclear export, translation, and mRNA stability and decoy, thereby influencing multiple biological processes, including stress responses, cell differentiation, and embryonic development [ 20 , 21 ]. Moreover, dysregulation of m 6 A has been reported in multiple types of cardiovascular diseases [ 22 ], including myocardial infarction [ 23 ], heart failure [ 24 ], cardiac hypertrophy [ 25 , 26 ], and atherosclerosis [ 27 , 28 ]. However, the etiological nature of m 6 A modification in DIC remains elusive.…”
Section: Introductionmentioning
confidence: 99%